Applied Microsoft Business Intelligence - LeBlanc, Patrick (Wiley, 2015)
Leverage the integration of SQL Server and Office for more effective BI Applied Microsoft Business Intelligence shows you how to leverage the complete set of Microsoft tools-including Microsoft Office and SQL Server-to better analyze business data. This book provides best practices for building complete BI solutions using the full Microsoft toolset. You will learn how to effectively use SQL Server Analysis and Reporting Services, along with Excel, SharePoint, and other tools to provide effective and cohesive solutions for the enterprise. Coverage includes BI architecture, data queries, semantic models, multidimensional modeling, data analysis and visualization, performance monitoring, data mining, and more, to help you learn to perform practical business analysis and reporting. Written by an author team that includes a key member of the BI product team at Microsoft, this useful reference provides expert instruction for more effective use of the Microsoft BI toolset. Use Microsoft BI suite cohesively for more effective enterprise solutions Search, analyze, and visualize data more efficiently and completely Develop flexible and scalable tabular and multidimensional models Monitor performance, build a BI portal, and deploy and manage the BI Solution